1996
DOI: 10.3177/jnsv.42.87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Egg White on Serum Cholesterol Concentration in Young Women.

Abstract: SummaryIn a previous study we observed favorable effects of egg white on serum lipids in rats and mice. The present study was designed to elucidate these effects in 24 female university students with moderate hypercholesterolemia. About 30% of total protein was supplied with egg white, tofu or cheese. The experiment was conducted for a complete menstruation cycle of each subject. Lipid intake was about 30% of total energy intake. The energy intake of each subject was constant throughout the experiment. Body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 37 publications
2
34
0
1
Order By: Relevance
“…When lipoprotein particle size and subclasses were analyzed by nuclear magnetic resonance (NMR), significant increases in both LDL and HDL particles as well as an increase in lecithin cholesterol acyltransferase (LCAT) activity were observed by whole egg consumption (16). It has also previously been reported that egg white protein lower the concentration of serum cholesterol by inhibiting cholesterol absorption in animal experiments and clinical trials (17,18). The lack of the increase of serum cholesterol could be attributed to the relatively low amount of loaded cholesterol and to the alteration of the absorption and reverse transport of cholesterol caused by egg components.…”
Section: Discussionmentioning
confidence: 99%
“…When lipoprotein particle size and subclasses were analyzed by nuclear magnetic resonance (NMR), significant increases in both LDL and HDL particles as well as an increase in lecithin cholesterol acyltransferase (LCAT) activity were observed by whole egg consumption (16). It has also previously been reported that egg white protein lower the concentration of serum cholesterol by inhibiting cholesterol absorption in animal experiments and clinical trials (17,18). The lack of the increase of serum cholesterol could be attributed to the relatively low amount of loaded cholesterol and to the alteration of the absorption and reverse transport of cholesterol caused by egg components.…”
Section: Discussionmentioning
confidence: 99%
“…The apparently complex effects and mechanisms involved in the cholesterolemic responses to other dietary animal proteins have yet to be completely elucidated. Recent studies have confirmed that a hypocholesterolemic action can be found in animal proteins such as milk whey protein 5,6) and egg white protein 7,8) comparable to that of milk casein.…”
mentioning
confidence: 85%
“…On the other hand, some reports have been published on the hypocholesterolemic effect of animal products, such as egg white protein, 14) papain-hydrolyzed pork meat, 15) and peptides derived from bovine milk betalactoglobulin. 16) Animal liver has traditionally been used as a food ingredient to supply several nutrients.…”
mentioning
confidence: 99%